STUDENT LEARNING DIFFICULTIES IN GENETICS COURSES - Dewi Murni; Iing Dwi Lestari (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2023)
This research aims to determine students' difficulties in Genetics Course. The descriptive method was used in this study. The research sample was 85 Department of Biology Education students enrolled in the Genetics course. The instrument used was cognitive tests and questionnaires with content questions concerning students' learning difficulties. Cognitive test results showed an average value of 49.5, with a highest score of 90 and the lowest was 11. 52% of the students suggested the Genetics course is a tricky subject. The most crucial factor of learning difficulties is inappropriate learning style (66.3%), Genetics characteristics (65,8%), and lack of infrastructure (65.8%). The most challenging topics in genetics are linkage, crossing over, and chromosomes mapping (26.9%). This result is consistent with the questionnaire that 30% of the students stated that these topics are the most difficult in Genetics.